Trace element analysis of food and diet - Aras, Namık K. (RSC Pub., 2006)
Trace element analysis has a key role to play in quality control of food and diet. This timely book introduces the subject in a practical way, from sampling and the techniques available for trace analysis, through procedures for specific elements and analysis of the data.Beginning with a brief introduction and discussion of statistical evaluation of data, the subsequent chapter looks at trace analysis in general, with its essentials and terminology. Another section introduces sampling and preparation of foodstuffs such as wheat, potato, vegetables and milk. This is followed by descriptions of.
Keywords: Trace elements.; Trace elements in nutrition.; Food -- Analysis.; elektronické knihy; electronic books